1991
DOI: 10.1111/j.1751-8369.1991.tb00675.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose dependent effects of plumage-oiling on thermoregulation of Common Eiders Somateria mollissima residing in water

Abstract: Thermoregulatory effects which occur during the first hours after plumage‐oiling were studied under laboratory conditions by measuring the metabolic heat production of Common Eiders (Somateria mollissima) which were resting in water for up to three hours. The ducks were exposed to 10‐70 mL Statfjord A crude oil while residing in water inside a respiration chamber at 5.5°C. The study demonstrated a dose‐and time‐dependent effect of plumage oiling on metabolic heat production during the first three hours after c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Birds exposed experimentally to oil for only a few hours showed increases in heat production and thermal conductance even at room temperature (McEwan and Koelink, 1973;Erasmus et al, 1981). Jackass penguins (Spheniscus demersus) with environmental oil exposure covering up to 70% of their bodies had a 2.5 o C drop in body temperature after only 15 min in water at 19.5-20.5 o C. In water temperatures of 4.5-6 o C, common eiders (Somateria mollissima) exposed to 70 ml of oil became hypothermic in only 70 min (Jenssen and Ekker, 1991). Sanderlings (Calidris alba) with 20% oil coverage of their feathers spent significantly more time preening and less time resting and were more aggressive (Burger and Tsipoura, 1998).…”
Section: Thermoregulationmentioning
confidence: 99%
“…Birds exposed experimentally to oil for only a few hours showed increases in heat production and thermal conductance even at room temperature (McEwan and Koelink, 1973;Erasmus et al, 1981). Jackass penguins (Spheniscus demersus) with environmental oil exposure covering up to 70% of their bodies had a 2.5 o C drop in body temperature after only 15 min in water at 19.5-20.5 o C. In water temperatures of 4.5-6 o C, common eiders (Somateria mollissima) exposed to 70 ml of oil became hypothermic in only 70 min (Jenssen and Ekker, 1991). Sanderlings (Calidris alba) with 20% oil coverage of their feathers spent significantly more time preening and less time resting and were more aggressive (Burger and Tsipoura, 1998).…”
Section: Thermoregulationmentioning
confidence: 99%
“…Exposed birds were observed shivering and microscopic feather inspection revealed that barbules of oiled feathers were matted into clumps leading the authors to conclude that disruption of the smooth, organized structure of feathers caused water to penetrate the plumage. Jenssen and Ekker (1991) found that metabolic heat production of common eiders (Somateria mollissima) resting in 5.5 o C water for three hours after external application of 10 to 70 mL of crude oil increased over time and with dose, and that there was no change in metabolic rate at the low dose of 2.5 ml. Eiders are a large, wellinsulated northern bird and any impacts of oiling found in eiders likely would be as bad or worse in other smaller, or less insulated seabirds (Robertson et al 2014).…”
Section: Metabolic Ratementioning
confidence: 98%
“…Preening can result in eventual, effective removal of oil from plumage for some birds, primarily those with access to land and warmer climates; however, behavioural changes during the cleaning time and toxic effects from ingestion pose serious threats to survival and reproduction for many marine bird species. Yet, another study found that preening resulted in greater effects than oil left alone on the feathers since preening resulted in oil being spread around and into feathers, enhancing metabolic heat loss (Jenssen and Ekker 1991).…”
Section: Behavioural Effectsmentioning
confidence: 99%
“…Assuming that the heat capacity and mass remain constant, we may solve for body temperature as a function of time (Equation 3 in Table 2). 2001Thickness Δx Jenssen and Ekker (1991) PBOM = physiologically based oiling model; COEI = common eider; SPSA = spotted sandpiper; DOVE = dovekie; GBHE = great blue heron; AWPE = American white pelican; k = thermal conductivity in W/mK; ρ = density in kg/m3; Q = heat transfer in W; ΔT = thermal gradient in K; c = specific heat capacity in J/kg K; h = latent heat of vaporization in J/kg; Δhr = humidity ratio, unitless.…”
Section: Submodels In the Pbommentioning
confidence: 99%
“…Ambient air temperature was maintained at 5.5°C. Jenssen and Ekker (1991) reported that exposure to 10 to 15 mL oil resulted in a "small, transient rise in heat production." Exposure to 35 to 50 mL oil resulted in an "immediate increase in heat production, which leveled off at approximately 2 to 2.5 times the baseline level."…”
Section: Validation Of the Pbom Against Empirical Datamentioning
confidence: 99%